Uma descrição semiótica da metáfora no ensino de biologia: asserções sobre a célula animal - Trevisan, Marlon Dantas [UNESP]; Carneiro, Marcelo Carbone [UNESP] (My University, 2010)
The main objective of this survey is describing signly the metaphor learning resource, with focus on biology education. Our teorical reference is the peircean semiotics, because it means solid heritage to code surveys implicated at science education, it led us to do an explanation about the main lines about that reference, addressed to researchers and lecturers interested in those reasonings. In the description yearned, another objectives appear: demonstrate diferences between metaphor/analogy and pragmatic analogy; to list metaphors, from cell representation analysis, and argue about principals diferences and probable cognitive consequences between the metaphor event in the visual representation and speech sentences. Therefore we analysed the animal cell of a high school first grade studying book – biology – cell biology – used by São Paulo and another state students. The findings demonstrate the undeniable importance of the metaphor as a learning tool in the biology education, and new findings about that, such as its limits in the concept elaboration, gnosiologic consequences for receptioning, the search needs for propositions– pictures between concept relations – in the science speech construction, and other results.

Este artigo tem como principal meta descrever semioticamente o recurso pedagógico da metáfora, em especial no ensino de biologia. Nosso aporte teórico é a semiótica peirceana, posto que esta representa sólida herança aos estudos das linguagens implicadas no ensino de ciências, o que nos levou a fazer uma exposição sobre as linhas gerais daquele referencial, voltada aos pesquisadores e educadores interessados nessas reflexões. Na descrição pretendida, outros objetivos se nos apresentam: assinalar diferenças entre metáfora/analogia e a analogia pragmática; enumerar metáforas, a partir da análise da representação de uma célula, bem como discutir as diferenças mais evidentes e possíveis implicações cognitivas entre a ocorrência da metáfora na representação visual e em enunciados linguísticos. Para tal, analisamos a ilustração da célula animal de uma apostila de 1º. ano de ensino médio - biologia - citologia - utilizada por estudantes de São Paulo e outros estados. As conclusões obtidas expressam a inequívoca importância da metáfora como ferramenta didática no ensino de biologia, bem como novas inferências sobre a mesma, tais como seus limites na construção de conceitos, implicações gnosiológicas para a recepção, a necessidade de se buscarem proposições – associações de imagens a conceitos – na construção do discurso científico, entre outras contribuições.
A description of the semiotic metaphor in biology teaching: assertions about the animal cell
Keywords: Metaphor; Semiotics; Sign; Picture; Speech sentence; Metáfora; Semiótica; Signo; Ilustração; Enunciado linguístico